Furosemide is associated with acute kidney injury in critically ill patients - Levi,T.M. (2012)
Acute kidney injury (AKI) is common in critically ill patients. Diuretics are used without any evidence demonstrating a beneficial effect on renal function. The objective of the present study is to determine the incidence of AKI in an intensive care unit (ICU) and if there is an association between the use of furosemide and the development of AKI. The study involved a hospital cohort in which 344 patients were consecutively enrolled from January 2010 to January 2011. A total of 132 patients (75 females and 57 males, average age 64 years) remained for analysis. Most exclusions were related to ICU discharge in the first 24 h. Laboratory, sociodemographic and clinical data were collected until the development of AKI, medical discharge or patient death. The incidence of AKI was 55% (95%CI = 46-64). The predictors of AKI found by univariate analysis were septic shock: OR = 3.12, 95%CI = 1.36-7.14; use of furosemide: OR = 3.27, 95%CI = 1.57-6.80, and age: OR = 1.02 (95%CI = 1.00-1.04). Analysis of the subgroup of patients with septic shock showed that the odds ratio of furosemide was 5.5 (95%CI = 1.16-26.02) for development of AKI. Age, use of furosemide, and septic shock were predictors of AKI in critically ill patients. Use of furosemide in the subgroup of patients with sepsis/septic shock increased (68.4%) the chance of development of AKI when compared to the sample as a whole (43.9%).